On the existence of solutions of the differential equation with advanced argument - Muzyczka, Zofia (Annales Mathematicae Silesianae, 1985)
In this paper the differential-functional equation ϕ'(t) = f(t,ϕ), t∈R+ ϕ(0) = η with an unbounded advanced argument is discovered. Under suitable assumptions, using Schauder Fixed Point Principle, a theorem on existence of solutions in a special functional-space is proved.